Synthesis and Characterization of Some Mixed Ligand Complexes of Thorium(IV0 and Dioxouranium(VI) with Salicylylhydrazine and its Dervatives - Rajendran, G. (Asian Journal of Chemistry, 2010)
A series of 12 mixed ligand complexes of Th(IV) and UO2(VI) withsalicylylhydrazine (SH) and its derivatives as primary ligands and twodifferent anions, viz., nitrate and thiocyanate as secondary ligands havebeen synthesised and characterised on the basis of elemental analysis,molecular weight, molar conductance, IR spectral, TG and DTG data.These complexes have the general formulae [Th(LL)2(NO3)4],[Th(LL)2(NCS)4], [UO2(LL)2(NO3)2] and [UO2(LL)2(NCS)2] where LL= SH, ASH, BSH. In these complexes the primary ligands salicylylhydrazine(SH), acetyl salicylylhydrazine (ASH)' and benzoyl salicylylhydrazine(BSH) act as neutral bidentate ligand and the secondary ligands, viz., themonovalent anions NO3 - and NCS- act as unidentate ligands.